Penyakit Kering Pelepah pada Tanaman Kelapa Sawit di Provinsi Kalimantan Timur dan Sumatera Utara - Donnarina Simanjuntak; Agus Susanto (Jurnal Fitopatologi Indonesia, 2013)
The rapid development of oil palm industry is indicated by wide monoculture plantation. This condition causes the development of many diseases such as basal stem rot, bud rot, leaf spot, anthracnose, and fruit rot diseases. Recently, a new disease causing dry frond symptom was reported from plantations in 2 provinces, i.e. East Kalimantan and North Sumatera. Disease exploration was conducted in Muara Wahau estate, East Kalimantan and Kota Pinang (Labuhan Batu) estate, North Sumatera. Typical symptoms involved decaying which started from the tip of frond that spread into the middle, rotting brown to blackish; when rot had reached the middle, the frond becomes dry, and finally broken. Isolation and identification of the fungi from the infected plant showed the association of Thielaviopsis sp., although Koch Postulate–based assay was unable to prove that the disease was caused by infection of Thielaviopsis sp.